Sentencing Females Convicted of Sex Offenses: Examining Measures of Perceived Dangerousness and the Decision to Incarcerate. (January 2022) - Gibbs, Benjamin R.; Ten Bensel, Tusty
From media attention to legislative actions, individuals convicted of sex offenses are often perceived as dangerous and a threat to society. Previous research, however, has demonstrated that perceived dangerousness is gender-specific, often minimizing culpability for women convicted of sex offenses. Consequently, previous research on sentencing outcomes of these individuals have largely been male-only samples, leaving a gap in the literature as it pertains to females convicted of sex offenses. The current study sought to fill this gap by examining the impact that those convicted, victims, and offense characteristics had on sentencing outcomes for women convicted of sex offenses. We analyzed a sample of 262 females convicted of a sex offense in a Southern state. The results demonstrated that official case characteristics, along with victim characteristics, play an influential role in the judicial decision to impose an incarceration sentence.